Modeling the systemic trade risk of crude oil from a network perspective, combined with a sentiment proxy - Chang, Hao; Luo, Aiguo; Zheng, Yilin; Chang, Ridong; Liu, Yifan (Frontiers in Energy Research, 2023)
Trade networks of crude oil are susceptible to cascade of initial shocks that increase systemic trade risks and threaten energy security. This study introduces a novel method of modelling systemic trade risk of crude oil which is combined with a sentiment proxy from a network perspective. We construct sentiment instability to evaluate the uncertainty of crude oil trade in a country and use the PageRank algorithm to measure supplier diversity from a network perspective instead of direct trade partners. At the global level, we show that the distribution of systemic oil trade risk has an obvious heterogeneity and a significant negative correlation between systemic trade risk of crude oil and trade volume volatility. At the regional level, we compare the systemic trade risk of crude oil between China and America and systemic trade risks show strongly significant correlations with the price volatility in both China and America. Furthermore, the structure of trade network can effectively reduce the systemic risk in America while it increases the systemic trade risk in China. Our results can give a reason for an irrational practice of Chinese crude oil imports which are “buying when the price is rising and not buying when the price is declining”.